2016
DOI: 10.7862/rz.2016.hss.59
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Policy as a Determining Factor for Development of World Class-Clusters

Abstract: The article aims to characterize the significance of cluster policy (cluster-based policy) for the development of world-class clusters. It indicates that the clusters functioning in the European Union (EU) member states are of very diversified nature, which ensues, inter alia, from different conditions (endo -and exogenous) of their development. The evolution of the clustering concept contributed to a greater interest and engagement of governmental organizations of European, national and regional levels in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
(10 reference statements)
0
3
0
1
Order By: Relevance
“…Cluster policy plays an important role in the economic policy of the European Union. Many European countries perceive it as a significant tool for influencing the growth of entrepreneurship, innovation and competitiveness of regional and national economies (Bembenek et al, 2016;Pavelkova et al, 2019). The value of the conducted research is the identification of relevant strategic documents, the provisions of which make up the cluster policy in Poland, as well as its assessment in terms of the role and scope of impact on cluster organisations, and, consequently, the challenges posed by cluster managers.…”
Section: Resultsmentioning
confidence: 99%
“…Cluster policy plays an important role in the economic policy of the European Union. Many European countries perceive it as a significant tool for influencing the growth of entrepreneurship, innovation and competitiveness of regional and national economies (Bembenek et al, 2016;Pavelkova et al, 2019). The value of the conducted research is the identification of relevant strategic documents, the provisions of which make up the cluster policy in Poland, as well as its assessment in terms of the role and scope of impact on cluster organisations, and, consequently, the challenges posed by cluster managers.…”
Section: Resultsmentioning
confidence: 99%
“…podkarpackie) oraz Klaster Kotlarski (woj. wielkopolskie) 3 . Po drugie -był to czas rozpoznawania idei klasteringu, określania jej wizji i celów.…”
Section: Wprowadzenieunclassified
“…A number of researchers and politicians suggest, that the cluster internationalization provides new opportunities for cluster members, especially for cluster SMEs. It can help these kind of firms to improve their competitiveness and accelerate their presence in global value chains 4 . Studies on clustering have also shown that the idea of business cluster there is an interconnection between economic-production and socio-cultural conditions, which significantly contribute to business profitability 5 .…”
Section: Cluster Internationalization Through Network: Theoretical Fmentioning
confidence: 99%